Logistics process improvement of warehousing and picking in a colombian company textile sector (2014)
This research considers the design problem of distribution center and picking in a Colombian textile company. Through a literature review, the methodology for the design of the facility that best adjusts the company for minimize the time picking is set. As from the methodology selected the orders profiles is built, based on the characterization, the problems designing and picking is way comprehensive treated. Different scenarios of distribution center design and picking and routing policies are evaluated, in order to identify the influence of the scenarios and policies at time of picking and utilization factor of resources involved in the process. The results contribute to improvement of process indicators; it is reflected in operating costs and customer service.